Performance and emission evaluation of a single cylinder diesel engine running on palm oil methyl ester enriched with methyl oleate - Altaie, Mohamad A. Hasan (2016)
Biodiesel is a renewable, alternative diesel fuel derived from various oils or fats through transesterification. Biodiesel consists of alkyl esters of the parent oil. Palm oil methyl ester (PME) is a prominent biodiesel in Southeast Asian countries, such as Malaysia and Indonesia, which have a surplus production of palm oil. However, the methyl ester exhibits poor cold flow characteristics because of the substantial amount of saturated fatty acids in palm oil. By contrast, methyl oleate (MO) possesses excellent cold flow properties because of its highly unsaturated components. MO can be produced from low-cost raw materials that generally contain high amounts of oleic acid. In this study, various blends were prepared through enrichment of PME with MO under different volumetric ratios of PME80:MO20, PME70:MO30, PME60:MO40, and PME50:MO50 (vol/vol, %). The optimum blend with improved cold flow properties than neat PME was determined. The physicochemical properties of the PME-MO blends were also investigated and compared with those of neat PME. The cloud point, cold filter plugging point, and pour point of the blends significantly improved compared with those of the neat PME. The increasing enrichment proportion of MO in the PME-MO blends until 50% (vol/ vol, %) led to 70.38%, 91.69%, and 100% improvement in cloud point, cold filter plugging point, and pour point values, respectively, compared with those of the neat PME. Important fuel properties (i.e., cetane number, kinematic viscosity, density, gross heating value, net heating value, flash point, and acid value) were also examined. Furthermore, the oxidation stability of the PME-MO blends was assessed 5 months after blend preparation. All fuel properties of the blends were within the specified permissible limits of biodiesel standard (ASTM D 6751) and very stable; as such, the mixtures did not show rapid decrease in oxidation stability. The PME-MO blends that met the specifications of ASTM D 6751 were submitted for further investigation to determine the performance and exhuast emissions in a single-cylinder direct-injection diesel engine.. The parameters associated with engine performance included torque, brake power, brake specific fuel consumption, and brake thermal efficiency. The PME-MO blends yielded lower torques and higher brake specific fuel consumptions than petroleum diesel because of the lower calorific value of biodiesel. Moreover, the blends showed significantly reduced carbon monoxide (CO) and hydrocarbon (HC) emissions and exhaust gas temperatures (EGT). Increasing the MO proportion up to 50% (vol/vol, %) reduced CO, HC, and EGT to 71.50%, 37%, and 5%, respectively, which were lower than those of petroleum diesel.